Beginning Teachers’ Induction in Chile: The Perspective of Principals - Flores-Gomez, C (Routledge, 2017)
This case study investigated the role of school principals in the induction of beginning teachers in Copiapó, Chile. Building upon group and individual interviews, and review of extant literature, the following findings were established: (a) principals in this study expect beginning teachers to be fully formed as classroom teachers; (b) principals were unlikely to talk about induction practices that might help beginning teachers to learn pedagogical strategies for classrooms; and (c) principals’ induction practices focused on the symbolic role that principals play as the highest authority within the school which has little practical influence on helping beginning teachers to develop their pedagogy. Implications for policy and practice are discussed. © 2017 Informa UK Limited, trading as Taylor & Francis Group.